Nursing diagnoses in critically ill patients during the COVID-19 pandemic - Maria Gabryelle Jatobá Pereira de Brito; Suelayne Santana de Araújo; Maria Einara Ferreira de França; Cláudia Gabrielle da Silva; Antonio Wellington Vieira Mendes; Diego Rislei Ribeiro; Cecília Maria Farias de Queiroz Frazão (Programa de Pós Graduação em Enfermagem da Universidade Federal do Piauí, 2024)
Objective: To verify the association between NANDA International nursing diagnoses and their elements in critically ill patients during the COVID-19 pandemic. Methods: Descriptive study that analyzed 60 medical records of patients admitted to the reference intensive care unit for COVID-19 in Pernambuco between August and October 2020. The data was analyzed using descriptive and inferential statistics. The study was approved by the ethics committee under number: 4.199.128. Results: The diagnosis "Ineffective airway clearance" was associated with the element "infection", while "Deficit in self-care for dressing" was associated with all its defining characteristics and the related factors: "Discomfort" and "Pain". "Risk of aspiration" was associated with the elements: ineffective coughing, enteral feeding, impaired ability to swallow, decreased level of consciousness and the presence of a nasal/oral tube. Altered skin characteristics, edema, diabetes mellitus and hypertension were associated with "Ineffective peripheral tissue perfusion". "Dysfunctional response to ventilatory weaning" was associated with nine of its elements. Conclusion: There were associations between five NANDA International nursing diagnoses and their elements in critically ill patients during the COVID-19 pandemic. This enables the implementation of qualified care focused on the real needs of patients.